DETERMINATION OF MERCURY AUTHORITY IN WATER, SEDIMENT, AND BLOT A WATER CAPUAS WATER WITH TECHNOLOGY AN NEUTRON ACTIVITY ANALYSIS (APN) - Yusman Wiyatmo; Bambang Ruwanto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2005)
The aim of this research were: 1) to determinate mercury disposition in water, sedimen, and biota in Kapuas river, and 2) to evaluate whether mercury disposition of the sample have been exceeded the threshold value which permitted to be consummed by animal an human. The sample of this research were water, sediment, and biota (algae and fish) in Kapuas river.The research was carried out by experiment with neutron activation analysis (NAA) method The determination of the elements in sample was conducted by gamma spectroscopy. The mercury disposition in sample was determined by comparing the cps of sample and the cps of standard (20 ppm). The results showed that the mercury disposition in water at TPI pier, KPLP pier, Dephub pier, and Kampung Mendawai were 0,25 ppm,0,14 ppm, 0,19 ppm, and 0,09 ppm respectively. The mercury disposition at sediment in TPI pier and Dephub pier were 1.56 ppm0.63 ppm respectively. on the other hand the disposition of the mercury in KPLP pier and Kampung Mendawai were not detectedThe mercury disposition at algae in a cross of Pertamina office, Taman Alun-Alun Kapuas, Kapuas bridge, and near Sudarso hospital were 0,41 ppm, 0,59 ppm. 0.58 ppm, dan 0,68 ppm respectively.Keywords: The mercury disposition, water, sediment, water biota. andNAA.